A analysis follow Speech and Function speech Expressive in the Tonight Show Program on Net TV: Pragmatic Studies (Journal of Social And Education Research, 2023)
Study aim For describe follow speech and function speech expressive in the Tonight Show on Net TV: Pragmatic Studies . Research data sources This are recorded data , technique , see , technique note in the Tonight Show on Net TV. Research data This is follow speech and function speech expressive in the Tonight Show on Net TV. Method study This use method descriptive with method collect data, describe data, and analyze data. Instruments used in study This is guidelines documentation . Data analysis technique used is listening , recording , taking notes , and describing follow speech and function speech expressive in the Tonight Show on Net TV. Research results This found follow said locution as many as 4 data, follow said illocutionary as many as 3 data, and follow said perlocutionary as many as 3 data while speech expressive say Happy as much as 2 data, speech expressive say accept love as many as 3 data, utterances expressive blame as many as 3 data, utterances expressive praise as much as 2 data, and speech expressive make fun of as many as 4 data.